2011
DOI: 10.1371/journal.pone.0020099
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Suppresses β-Catenin-Dependent Tolerogenic Activation Program in Dendritic Cells

Abstract: The mechanisms that underlie the critical dendritic cell (DC) function in maintainance of peripheral immune tolerance are incompletely understood, although the β-catenin signaling pathway is critical for this role. The molecular details by which β-catenin signaling is regulated in DCs are unknown. Mechanical disruption of murine bone marrow-derived DC (BMDC) clusters activates DCs while maintaining their tolerogenic potential and this activation is associated with β-catenin signaling, providing a useful model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…and M.B., unpublished data, 2012). 26,27 Incubation of pp65 or pp65-IC did not result in overt increase of the costimulatory markers CD40, CD80, or CD86, with only a minor increase in CD86 expression in pp65-IC treated MoDCs. Therefore, we concluded that increased cross-presentation of pp65-IC is not caused by increased costimulatory molecule expression.…”
Section: Potentiation Of Viral Antigen Cross-presentation By Fc␥r Tarmentioning
confidence: 85%
“…and M.B., unpublished data, 2012). 26,27 Incubation of pp65 or pp65-IC did not result in overt increase of the costimulatory markers CD40, CD80, or CD86, with only a minor increase in CD86 expression in pp65-IC treated MoDCs. Therefore, we concluded that increased cross-presentation of pp65-IC is not caused by increased costimulatory molecule expression.…”
Section: Potentiation Of Viral Antigen Cross-presentation By Fc␥r Tarmentioning
confidence: 85%
“…This phenotype is similar to LCs from tamoxifen-treated TGF-β and TGF-βRII mice. Indeed, TGF-β has been shown to inhibit the noncanonical β-catenin pathway (29). One relatively unique aspect of this system is that TGF-β acts in an autocrine/ paracrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…␤-catenin is thus a necessary component of the signaling pathway induced by mechanical signals, and such pathway can be blocked by TGF-␤. 75 Based on these observations, Jiang et al suggested that the disruption of E-cadherin-mediated DC interactions constitutes one of the sterile triggers capable of generating tolerogenic DCs under steady-state conditions. 36 In that model, immunogenic TLR-mediated signals prevail over the E-cadherin-␤-catenin-mediated tolerogenic signals.…”
Section: Regulation Of E-cadherin/␤-catenin Function Influences the Dmentioning
confidence: 99%
“…36 This ␤-catenin-mediated induction of tolerogenic DC is inhibited by TGF-␤. 75 (C) E-cadherin is a selective marker for IL-4/IL-13-exposed macrophages and is STAT6/DAP12/polyamine-dependently induced. 90 For personal use only.…”
Section: E-cadherin As Marker For Colitogenic Dcsmentioning
confidence: 99%